The Problematics of the Legal Standing of Deoxyribonucleic Acid (DNA) Test Results Concerning Civil Relationships of Illegitimate Children: A Legal Pluralism Perspective - Fradhana Putra Disantara; Dicky Eko Prasetio; Geraldha Islami Putra Disantara; Briggs Samuel Mawunyo Nutakor (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
Decision No. 46/PUU-VIII/2010 by the Constitutional Court has introduced legal challenges, particularly concerning the acceptance of DNA testing as evidence for establishing civil relationships between a child and their biological parent. This study aims to analyze the legal issues surrounding the use of DNA testing to prove civil rights of illegitimate children and the aspects of legal pluralism related to this use. The research employs a normative legal approach, utilizing case, conceptual, and legislative analyses. Findings indicate that the legal issues with DNA testing for establishing the civil rights of illegitimate children stem from the Constitutional Court's decision, which has not fully considered the legal pluralism perspective, leading to potential application challenges. Post-decision, DNA testing reflects a weak legal pluralism where the Court's ruling is not easily applicable due to conflicts with Islamic law as outlined in Article 100 of the Compilation of Islamic Law (KHI). Consequently, it is recommended that the Constitutional Court and judicial institutions consider legal pluralism aspects in their decisions to strengthen legal pluralism, ensuring that court rulings are optimally implemented in alignment with existing and practiced legal frameworks within society.